HISTOLOGICAL PRESENTATION OF BREAST CANCER AND ITS ASSOCIATION WITH METABOLIC SYNDROME - Matluba A. Mirzaeva; Bakhtiyor U. Iriskulov; Lola T. Alimkhodjaeva (Central Asian Journal of Medicine, 2023)
Backgrounds. Metabolic syndrome(MS) is associated with an increased risk of cardiovascular disease, type II diabetes, and recurrence of disease in breast cancer(BC) patients. In this cross-sectional study, we analyzed the histological demonstration of MS-associated BC. Methods and materials. We interviewed 74 women with diagnosed breast cancer at the Republican Cancer Center in Uzbekistan. All MS criteria were evaluated in every patient, and the histological performance of the tumors was based on pathomorphological analysis. Results. 41 of 74 patients have three or more MS elements. In these groups, diversified histological types of tumors occur. Tumor size is the most significant, and proliferative activity of tumor cells is higher than in the group without MS. Triple negative molecular subtypes occur more in women who have MS. We didn’t find significant differences in other histological criteria between the two groups. Conclusion. MS can affect some histological demonstrations of BC, such as tumor size, tumor histological types and subtypes, and cancer cell proliferation activity.